Monetary and credit policy of Ukraine: Current trends and challenges - Natalia Chyzh; Оksana Urban (Економічний форум)
The article examines the modern problems of monetary policy formation by the National Bank of Ukraine in the conditions of war, and also defines the specifics and peculiarities of the functioning of the financial market and the banking sector in the sphere of lending to the economy. The dynamics of money market indicators since the beginning of Russia's aggression have been studied, and the reasons and consequences of their changes in terms of impact on economic activity in the country have been clarified. The main goal of the study is to determine the current trends of monetary policy in Ukraine in the context of ensuring the maximum effectiveness of its influence on the formation of prerequisites for the growth of the national economy in future periods. The systematization of literary sources and approaches to solving the problem of the formation of an effective monetary policy of the state in crisis conditions indicates that this issue requires in-depth research, since scientific and practical developments related to ensuring the normalization of the monetary and credit system in conditions of military aggression are currently is not enough for a full understanding of the methods of regulating the money market. The urgency of solving this scientific problem lies in the fact that there is an objective need to ensure the effectiveness of the functioning of the national economy of Ukraine in the difficult conditions of the war, which cause structural deformations in the money markets. The object of the study is the monetary policy of the National Bank of Ukraine, because it determines the supply of money on the market, which in turn affects the amount of resources available to the banking sector for lending to the national economy. The article presents the results of an empirical analysis of the indicators of the money market, which showed that there is currently a reduction in the supply of available resources on the part of commercial banks due to the increase in the NBU discount rate and a significant increase in the risk of borrowers' creditworthiness. The study empirically confirms and theoretically proves that it is necessary to make adjustments to the policy of the NBU to stimulate lending to the real sector of the Ukrainian economy